Risk of cancer for arc welders in the Federal Republic of Germany: results of a second follow up (1983-8). Issue 10 (October 1991) - Becker, N; Chang-Claude, J; Frentzel-Beyme, R
Abstract : An extended follow up of 1221 chromium and nickel exposed welders in the Federal Republic of Germany confirmed an increased relative risk of 1.6 for all cancers compared with an internal reference group of 1694 turners. In an external comparison an excess of deaths from malignant tumours compared with that expected from the national mortality rates was found (standardised mortality ratio (SMR) = 109), which was clearly related to both time since first exposure and duration of exposure. Mortality from lung cancer was increased among welders (SMR = 113) but also among turners (SMR = 108). The difference remained when the subgroups were compared according to smoking information. A large excess of mesothelioma as a cause of death could be attributed to exposure to asbestos. The significantly increased SMR seen for urogenital tumours and "other or unspecified tumours" showed, however, an inverse relation with time since first exposure. This and other inconsistencies in the analysis by type of welding do not permit conclusive statements. Thus a further extension of follow up seems warranted.